Implementation of Minister of Tourism Regulation No. 10 of 2019 on Tourism Crisis Management in Bukittinggi City - Muhammad Habibi; Putri Febri Wialdi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research is grounded in the importance of implementing Regulation of the Minister of Tourism Number 10 of 2019 concerning Tourism Crisis Management as a guideline for anticipating potential crises that may affect the tourism sector. Bukittinggi, one of the leading tourist destinations in West Sumatra, is prone to natural hazards, which makes effective policy implementation essential. This study aims to analyze the implementation of the regulation in Bukittinggi City and to identify the supporting and inhibiting factors of its implementation. A qualitative descriptive method was employed, with data collected through interviews, observation, and documentation, and analyzed using the Miles and Huberman technique. The analysis of policy implementation refers to George C. Edward III's model, covering communication, resources, disposition, and bureaucratic structure. The results show that the implementation of the regulation in Bukittinggi City has run reasonably well; the four dimensions have generally supported its execution, although constraints remain, including limited resources, suboptimal socialization to all stakeholders, and the need for stronger crisis-management coordination. Supporting factors include local government commitment, inter-agency coordination, and stakeholder support, while a dedicated crisis-management team, standard operating procedures, and a specific budget have yet to be established. Strengthening coordination, resource capacity, and preparedness is therefore needed to achieve a more effective tourism crisis management system in Bukittinggi City.